Estructuras de desigualdad laboral en el principal enclave aguacatero mexicano - Saldaña Contreras, José Luis (Pontificia Universidad Católica del Perú, 2025)
This study analyzes structural inequality in employment within the avocado agro-industrial enclave of Michoacán, Mexico. It examines income distribution asymmetries, labor segmentation mechanisms, and heterogeneity in contractual conditions, among other aspects. Through a mixed-methods research design, quantitative analyses (indices and coefficients) are integrated with qualitative evidence obtained from interviews and ethnographic observation. The findings indicate a concentration of surplus among large producers and traders, while a significant number of agricultural workers face labor precarity and limited access to formal employment and social security schemes. The study concludes that the agro-export specialization, structured as a productive enclave, has perpetuated structural inequalities and a dependency position, expressing the need for public policy interventions and other measures to reduce these disparities.

En el presente estudio se analiza la desigualdad estructural del empleo que se genera en el enclave agroindustrial aguacatero de Michoacán, México. Se examinan las asimetrías en la distribución del ingreso, los mecanismos de segmentación laboral y la heterogeneidad en las condiciones contractuales, entre otros aspectos. A través de un diseño metodológico mixto, se integran análisis cuantitativos (índices y coeficientes) con evidencia cualitativa obtenida de entrevistas y observación etnográfica. Los hallazgos apuntan hacia una concentración del excedente en grandes productores y comercializadores, mientras que una gran cantidad de trabajadores agrícolas enfrentan una precarización laboral y limitado acceso a esquemas de formalidad y de seguridad social. Se concluye que la especialización agroexportadora, en forma de enclave productivo, ha perpetuado las desigualdades estructurales y una posición de dependencia, por lo que se requieren intervenciones de política pública y otras acciones para reducir las brechas.
Structures of Labor Inequality in the Main Mexican Avocado Enclave
Keywords: Structural gaps; Labor segmentation; Avocado agro-industry; Productive enclave; Brechas estructurales; Segmentación laboral; Agroindustria aguacatera; Enclave productivo; https://purl.org/pe-repo/ocde/ford#5.04.00